The life history narrative of clinical nurses with more than 30 years of experience - Bong Ja Shin; Eun Young Park (BMC, 2022)
Abstract Background The nurses with long-term careers in clinical settings shows a clear declining trend. Recording the specific period in Korea's nursing history is also important from a historical perspective. The aim of this study was to analyze the life history narrative of clinical nurses who have been in service for more than 30 years and to explore the strength and structure of their experience that enabled them to retain their long-term careers. Methods This study conducted qualitative research with a life history narrative. For data collection, biographical-narrative interview through in-depth personal interviews with six participants. The participants were clinical nurses who had worked at a general hospital for more than 30 years. The interviews were conducted in three sessions per participant, each session lasting 90-180 min. Qualitative thematic analysis was used to analyze the data. Results The narrative of their life stories were analyzed by dividing them into "Dimensions," "Turnings" and "Adaptations". The dimensions were categorized into individual and career dimensions. Turning points were empirical and environmental conditions that posed a threat to their career retention as nurse clinicians. Adaptations were illustrated individual methods and social interactions. Twenty-four themes were derived from the 94 thematic statements. After the abstract, four comprehensive categories emerged. The core theme for retaining long-term careers, with "Finding value in myself" comprising four themes: "acknowledgement and support from families," "healthy relationship at work," "trusting myself'," and "accumulation of small achievements." Conclusions The life narratives of participants reveal a close connection with and relationship between the changes in the social aspects, the fields of healthcare and nursing, their individual predispositions, family recognition, and organizational support at that time in Korea. The healthy interpersonal relationships in work place are the most important condition in maintaining the long-term work of nurses. The experience of nurses in one era may not be able to represent experiences in another era, so an in-depth study exploring the social context seems to be necessary. There is a need for policies and changes in the field that can keep the lives of professional women working as nurses proudly.